ANEMIA FALCIFORME: UMA REVISÃO NARRATIVA DOS AVANÇOS, DESAFIOS E PERSPECTIVAS FUTURAS - Medeiros, Adriane Menezes De (2024)
Sickle cell anemia (SCA) is a genetic disease characterized by the presence of hemoglobin S (HbS), leading to the formation of sickle-shaped red blood cells and resulting in a range of clinical complications. This narrative review addresses recent advances in understanding and managing SCA, highlighting general aspects of the disease, nutritional challenges, psychosocial issues, and new therapies. Advances in the understanding of pathophysiology, diagnosis, and treatment, including pharmacological therapies and emerging therapeutic approaches such as gene therapy and genetic editing, offer hope for improving health outcomes and quality of life for patients with SCA. However, persistent challenges such as malnutrition, psychosocial issues, and disparities in access to treatment remain significant obstacles. A multidisciplinary and holistic approach is essential to address these challenges and improve outcomes for individuals affected by this debilitating disease.